IMPLEMENTASI PENDIDIKAN BERBASIS TEKNOLOGI UNTUK MENINGKATKAN KESADARAN DIGITAL DAN LINGKUNGAN DI DESA BOGAK KABUPATEN BATU BARA - Laila Fidia Salam; Vindi Aulia; Aulia Sahpitri; Rizki Ananda Rahmansyah; Grace Stefani Sembiring; Nazriani Lubis (LPPI UMN AL WASHLIYAH, 2026)
The rapid development of information technology in the era of the Industrial Revolution 4.0 demands improved digital literacy among all groups, including students in rural areas. The Community Service Program (KKN) conducted by students of Universitas Muslim Nusantara Al Washliyah in Bogak Village, Tanjung Tiram Subdistrict, Batu Bara Regency, aimed to enhance digital literacy through training on the use of Canva for students of SMP Negeri 2 Bogak. This program also integrated technological education with environmental values to foster creativity, critical thinking, and ecological awareness.The method applied was experiential learning consisting of five stages: introduction, socialization, material delivery, practice, and evaluation. A total of 30 eighth-grade students actively participated in the training. The results showed significant improvement in students’ digital skills, creativity in producing environment-themed designs, and confidence in expressing ideas through visual media. However, several challenges were encountered, including limited internet access, lack of digital devices, and insufficient teacher training in technology use. Overall, the program demonstrates that integrating technology-based learning with environmental education can serve as an effective strategy to improve educational quality and shape the character of young generations in coastal areas.